Decision Support System for Prioritising the Use of Village Funds in Improving Local Infrastructure Using the Analytic Hierarchy Process (AHP) Method - Rizqi, Alif Faiq; Aspriyono, Hari; Suryana, Eko (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study discusses the development of a Decision Support System (DSS) to assist the Karya Bakti Village government in determining priorities for the use of Village Funds for local infrastructure development. The background of this research stems from a common problem in villages, namely suboptimal fund allocation due to subjective and conventional decision-making processes. The objective of this research is to design a DSS based on the Analytic Hierarchy Process (AHP) method so that decision-making becomes more objective, measurable, and in line with the urgent needs of the community. The benefits of this research are expected to assist the village in determining infrastructure development priorities and serve as a scientific reference for academics or researchers in similar fields. The results of this research are a web-based system that has been successfully developed and tested using the black box method, with all features functioning as intended. This system facilitates the comparison process between criteria and infrastructure project alternatives using AHP, and produces clearer and more measurable development priorities. In conclusion, the application of this DSS has proven effective in improving transparency and efficiency in decision-making at the village level, and has the potential to be applied to other villages with adjustments to local characteristics.